In vitro interactions of amphotericin B and non-antifungal compounds against opportunistic human pathogen Cryptococcus neoformans - Szerencsés Bettina (Acta biologica Szegediensis, 2019)
The incidence of opportunistic human pathogen Cryptococcus neoformans caused infections have been higher during the last few decades along with the increasing number of susceptible individuals around the world. Recommended treatment of cryptococcal meningoencephalitis is a combined therapy with amphotericin B deoxycholate and flucytosine. Despite of the efficiency of this drug combination, the mortality rate of the disease is high due to the limited accessibility and the high cost of these antifungals in the most severely affected areas. The broad-spectrum activity of non-antifungal drugs and their potential to enhance the efficiency of conventional antifungal agents have been recognised previously. In this study, the in vitro activity of amantadine, valproic acid, trifluoperazine and chlorpromazine was tested against five C. neoformans strains individually and in combination with amphotericin B. All the four compounds exerted slight antifungal activity against the studied C. neoformans strains. Their combination with amphotericin B revealed additive and synergistic interactions.